2018
DOI: 10.18843/ijms/v5i2(7)/01
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Role Overload on Job Stress, Job Satisfaction and Job Performance-A study among Married Working Women in Banking Sector

Abstract: Globalization fostered competition in every field

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 3 publications
9
30
1
2
Order By: Relevance
“…The study also found that technology‐based job overload had a positive significant relationship with turnover intention (see hypothesis testing in Table ). The results of the study are in line with what has been found in previous research on job overload and turnover (Mittal & Bhakar, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study also found that technology‐based job overload had a positive significant relationship with turnover intention (see hypothesis testing in Table ). The results of the study are in line with what has been found in previous research on job overload and turnover (Mittal & Bhakar, ).…”
Section: Discussionsupporting
confidence: 92%
“…(Carstens et al, ) identified that work overload will be avoided when providing the employee with resources that are needed to do a job; this can also be viewed as an important factor in an employment relationship. These resources make the employees’ work overload easier and more manageable and also allow workers to be more productive (Mittal & Bhakar, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, this notion strengthened the idea to study RS in the context of service sector (Malik et al, 2010). The results of this research on direct effects are in-line with the existing theoretical framework of RS (Mardhiah & Choi, 2015; Mittal & Bhakar, 2018; Sharma, 2007; Yaacob & Long, 2015). They show that service sector employees with higher levels of RS are less satisfied and less committed with their job as well as they are less likely to maintain their membership in an organization.…”
Section: Discussionsupporting
confidence: 85%
“…These results are consistent with previous research (Alon, Doepke, Olmstead-Rumsey, & Tertilt, 2020;Wenham, Smith, & Morgan, 2020) that have already shown the impact of gender in crisis situations. Women are exposed to several psychological vulnerability factors that may aggravate the levels of anxiety associated with COVID-19, such as domestic violence (Garcia-Moreno, Heise, Jansen, Ellsberg, & Watts, 2005), work overload (Mittal & Bhakar, 2018), and discrimination (Parashar, 2020). The CAS proved to be sufficiently sensitive to assess these differences, which had been observed in those studies.…”
Section: Discussionmentioning
confidence: 99%